APProve: Facilitating Active Monitoring, Versioning and Provenance Tracking of Data Management Plans - Gomes Pinheiro, Annatercia; Machado Campos, Maria Luiza; Serra da Cruz, Sérgio Manuel (Journal of Information and Data Management, 2025)
As modern societies become increasingly data-driven, reliance on research data generated by complex experimental setups and scientific systems has grown. However, applying this scientific knowledge to diverse contexts can be challenging. This paper introduces the Active Plans Provenance (APProve) framework, which offers solutions and mechanisms to monitor variations and trace the lineage of Data Management Plans (DMPs) in a simple and dynamic manner. APProve facilitates the synchronized evolution of DMPs with research projects, ensuring accessibility, shareability, and long-term maintainability for researchers. To assist researchers in tracking DMP versions, we developed a loosely coupled architecture that integrates seamlessly with traditional DMP generation tools. To evaluate the framework’s effectiveness, we conducted two distinct experiments, both involving DMPs generated by the ARGOS system. The initial experiment assessed APProve functionalities using a static DMP from the VODAN BR project. The second experiment analyzed an a-DMP from the OpenSoils platform project, a Brazilian soil data governance system. APProve empowers users to monitor changes, visualize version histories, and trace retrospective provenance related to DMP modifications. Additionally, it simplifies the DMP import process and provides comprehensive project visualization, including automated comparison of DMP versions across projects. The experiments demonstrated the framework’s efficacy in tracking and visualizing DMP version histories, thereby enhancing the management and evolution of these plans. In the VODAN BR case, APProve captured provenance details and enabled comparisons across revisions. For OpenSoils, the framework facilitated dynamic updates, ensuring alignment with ongoing project changes and highlighting discrepancies. Both cases confirmed APProve’s ability to improve accessibility and usability for researchers.